Antibacterial Activities of Novel Xestospongienol Compounds: Potential Natural Agents Against Vibrio sp. - Latifah, Lulu Adilla; Soekamto, Nunuk Hariani; Tahir, Akbar (Universitas Gadjah Mada, 2026)
The marine sponges, especially Xestospongia, belonging to the class Demospongiae, order Haplosclerida, family Petrosiidae, produce diverse bioactive secondary metabolites, which can be the source of potentially valuable marine natural products. These secondary metabolites could be used as alternative antibiotics to inhibit pathogenic bacteria Vibrio sp. This study aimed to isolate and characterize active compounds from Xestospongia testudinaria collected from Badi Island, South Sulawesi, Indonesia, and to evaluate their antibacterial potential. Research methods were evaporation, fractionation, purification, identification, and characterization of compounds using 1D and 2D NMR. Pure compounds were determined for their antibacterial activities using agar diffusion method against Vibrio harveyi M-120, Vibrio parahaemolyticus T-170, and Vibrio alginolyticus B-425. The fractionation and elucidation results presented two new compounds: xestospongienol, one of the types of brominated polyunsaturated acetylenic fatty acids (BPUFAs). The inhibition zone value of new compounds is 6.33–7.97 mm, where compound 2 showed higher activity than compound 1 against V. harveyi (7.97 mm). This study was the first report on the antibacterial activity of xestospongienol compounds against Vibrio sp., suggesting their potential as natural antibacterial agents.